CONSTRUCTION OF TOKOPEDIA SQUAD AD PUBLICITY DISCOURSE: A STUDY OF CRITICAL DISCOURSE ANALYSIS OF NORMAN FAIRCLOUGH - Tubagus Wijaya, Bagus (TALENTA, 2023)
Abstract The Tokopedia squad is a group of influencers formed by the Indonesian e-commerce giant Tokopedia in one of its advertisements. The Tokopedia Squad advertisement was uploaded with the headline â€œInspirational, update current products & tell you anti-stale promos!â€. Having the concept of a Squad or a team consisting of eleven well-known Indonesian influencers, Tokopedia Squad narrates the life of young people who have contemporary needs and can be accessed easily, practically, and instantly through the Tokopedia platform. Advertising publicity intends to promote a product to the intended target market. Advertising publicity that is carried out massively and carried out on a large scale certainly conveys discourse messages that contain ideology in them. The purpose of this study is to dissect the construction of discourse contained in the advertising publicity of Tokopedia Squad with the study of critical discourse analysis by Norman Faircligh, by looking at a textual discourse seen not only as text but as social practice. The method used is to look at three discursive dimensions starting from the text, text production, and sociocultural practices that build the discourse of the text. The results of the analysis found that the birth of text as a social practice was based on the socio-cultural conditions of Indonesia, especially millennial youth who are passionate about updates and technological matters. The ideology of convenience and consumerism aligns millennial youth which can be realized with the Tokopedia platform. Keywords: Discourse Construction, Tokopedia Squad, Publicity